PENERAPAN MEDIA INTERAKTIF GENIALLY UNTUK KEMAMPUAN ANALISIS SISWA PADA MATERI TEKS NARASI KELAS V - Tsania Prameswari; Heru Subrata; Ulhaq Zuhdi; Maryam Isnaini Damayanti; Heni Linawati (STKIP Subang, 2026)
This research is motivated by the low analytical skills of elementary school students in narrative texts, especially in identifying relationships between events, constructing storylines, finding causes of conflict, and interpreting the message of the story. One of the causes is the use of conventional learning media so that student engagement in the learning process is not optimal. Therefore, the interactive media Genially is implemented as an alternative learning that is more interesting, visual, and interactive. This research uses a descriptive qualitative approach with the aim of describing the use of Genially media in narrative text learning, student interaction patterns during learning, and obstacles faced in its application. The research was conducted on fifth-grade students of SDN Dukuh Pakis 1 Surabaya. Data were collected through observation, documentation, and interviews with the principal, class teachers, and students, then analyzed using the ATLAS.ti application through the stages of coding, categorization, reduction, data presentation, and drawing conclusions. The results of the study indicate that the use of Genially media is able to create more active, participatory, and enjoyable learning through the use of visuals, animations, quizzes, and educational games. The implementation of this media increased students' enthusiasm for participating in learning, discussing, and expressing opinions, as well as helping them understand elements of narrative texts such as characters, plot, conflict, and moral. Obstacles encountered included limited internet connection, readiness to use digital media, and some students' difficulty in explaining cause-and-effect relationships in the story. However, these obstacles were overcome through teacher guidance, group collaboration, and adjustments to learning strategies. Thus, the interactive media Genially has been proven to support increased student engagement and analytical skills in narrative text learning in elementary schools.